0
$\begingroup$

trying to follow a solution related to geometric series, but not sure what formula is used here. Any pointer is appreciated.Image here, can't embed image yet. I do try to plug in the Sn formula, but didn't get it to work

$\endgroup$
1
$\begingroup$

Notice:

$$3^n + 2(3^{n-1}) + 2^2 (3^{n-2}) + ... 2^{n-1}(3) + 2^n$$

can be effectively rewritten as

$$\sum_{k=0}^n 3^{n-k} \cdot 2^k = \sum_{k=0}^n 3^{n} \cdot 3^{-k} \cdot 2^k =\sum_{k=0}^n 3^{n} \cdot \frac{2^k}{3^k} = \sum_{k=0}^n 3^n \cdot \left( \frac{2}{3} \right)^k$$

This is a finite geometric series, then, with ratio $r=2/3$ and first term $2^03^n = 3^n$. The sum of a finite geometric series $a + ar + ar^2 + ... +ar^n$ is given by

$$\sum_{k=0}^n ar^k = \frac{a(r^{n+1} - 1)}{r-1}$$

Thus,

$$\sum_{k=0}^n 3^n \cdot \left( \frac{2}{3} \right)^k = \frac{3^n((2/3)^{n+1} - 1)}{2/3-1}$$

This is essentially the same expression as presented to you, just needing some manipulations to make the equivalence clear.

Multiply by $3$ on the top and bottom:

$$\frac{3^n((2/3)^{n+1} - 1)}{2/3-1} = \frac{3^{n+1} \cdot ((2/3)^{n+1} - 1)}{2 - 3}$$

Multiply by $-1$ on the top and bottom. We distribute this into the $()$ on top to reverse the order.

$$\frac{3^{n+1} \cdot ((2/3)^{n+1} - 1)}{2 - 3} = \frac{3^{n+1} \cdot (1 - (2/3)^{n+1})}{3 - 2}$$

Next:

$$1 - (2/3)^{n+1} = \frac{3^{n+1}}{3^{n+1}} - \frac{2^{n+1}}{3^{n+1}} = \frac{3^{n+1} - 2^{n+1}}{3^{n+1}}$$

The denominator cancels owing to the outside $3^{n+1}$ term, and of course $3-2=1$, leaving us with

$$\frac{3^{n+1} \cdot (1 - (2/3)^{n+1})}{3 - 2} = \frac{3^{n+1} \cdot \frac{3^{n+1} - 2^{n+1}}{3^{n+1}}}{1} = 3^{n+1} - 2^{n+1}$$

Thus,

$$3^n + 2(3^{n-1}) + ... +2^{n-1}(3) + 2^n = \sum_{k=0}^n 3^n \cdot \left( \frac{2}{3} \right)^k = 3^{n+1} - 2^{n+1}$$

$\endgroup$
  • $\begingroup$ It looks like your sum has an extra $(2/3)^k$ in it. $\endgroup$ – Michael Burr Dec 13 '18 at 3:32
  • $\begingroup$ Where, exactly? $\endgroup$ – Eevee Trainer Dec 13 '18 at 3:36
  • $\begingroup$ Oh, I see. I'll try to figure out how to resolve it. $\endgroup$ – Eevee Trainer Dec 13 '18 at 3:37
  • $\begingroup$ Okay, I believe I fixed it. It didn't really affect my approach, just more how it was being written in the summation. I suck at writing summations when they're a bit awkward like the one givenn. $\endgroup$ – Eevee Trainer Dec 13 '18 at 3:42
1
$\begingroup$

Sum of first n terms of a geometric series is given by:

$$S_n = \frac{a(r^n-1)}{r-1}.$$

Here $a$ is the first term of the series and $r$ is the common ratio.

In your question, $r = \frac{2}{3}$, $a=3^n$ and the number of terms is $n+1$ (you probably messed up in this part).

$\endgroup$
  • $\begingroup$ yes, did you notice that it was stated as $T(2^n)$ = ..., I do try to plug in the $S_n$ formula, but didn't get it to work $\endgroup$ – Maxfield Dec 13 '18 at 2:45
  • $\begingroup$ Perhaps it would be helpful to identify $a$ and $r$ in the given problem. $\endgroup$ – Michael Burr Dec 13 '18 at 2:46
  • $\begingroup$ as stated in the solution, r is 2/3 and, as a, which I can't find. but it states as T($2^n$) instead of $S_n$ though. $\endgroup$ – Maxfield Dec 13 '18 at 2:48
  • $\begingroup$ It doesn't matter what it is stated as. You can just calculate the sum of the RHS. (Also, see edit) $\endgroup$ – Nutan Nepal Dec 13 '18 at 2:54
0
$\begingroup$

One gets $T(2n)=3^n\sum_{k=0}^n(\frac23)^k=3^n(\frac{1-(\frac23)^{n+1}}{1-\frac23})=3^{n+1}-2^{n+1}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.